PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN LE MINERALE DI JAKARTA - Rahman, Arif; Ariandi, Fajri; Arista, Roynaldi; Chandra Utama, Dani; Warsono, Warsono (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of brand image and product quality on purchasing decisions of Le Minerale in Jakarta. In the increasingly competitive bottled water industry, brand image and product quality are important factors that can influence consumer perceptions and purchasing decisions. Brand image in this study refers to consumers’ perceptions of the Le Minerale brand, which are formed through experience, reputation, and trust in the product. Meanwhile, product quality includes aspects such as taste, safety, packaging, and production standards that affect consumer satisfaction. The research method used is a quantitative approach with a survey technique. Data were collected through a questionnaire distributed via Google Forms to consumers in Jakarta who have purchased or consumed Le Minerale products. The results show that brand image has a positive and significant effect on purchasing decisions. In addition, product quality also has a significant influence on purchasing decisions. Simultaneously, both brand image and product quality have a strong effect on increasing consumer purchasing decisions for Le Minerale. The implications of this study indicate that strengthening brand image and improving product quality are important strategies for companies to maintain and increase consumer purchasing decisions in the highly competitive bottled water market.